Effect of Topical Phytosterol Fraction of Chenopodium murale on Induced Hypertrophic Scar in Rabbits - Aya Ashraf Ahmed (Journal of Global Pharma Technology, 2020)
Objective: The present study aimed to evaluate the role of phytosterol fraction of Chenopodium murale in experimentally induced hypertrophic scar in rabbits. Methods: Surgical wound was performed on day 1 with an 8‑mm biopsy punch four wounds were created on the ventral surface of the rabbit ear (in vivo) down to cartilage. Triamcinolone acetonide (TAC) and phytosterol extracts of Chenopodium murale are administered topically to established scars on day 31. The outcome measures include the study of histopathology of skin section, transforming growth factor beta-1(TGF-β1) level and collagen III alpha in skin tissue. Results: The treatment groups produced high significant reduction in inflammatory scores, height, index of scar and in immunological scores of TGFβ1 and scores of collagen III in comparison with induced hypertrophic scar group (P≤0.001). Significant reduction was observed also in fibroblast count as compared with induced hypertrophic scar control group (P<0.05).Conclusion. Phytosterol extract of Chenopodium murale was effective in treatment of induced hypertrophic scar through its ability to produce reduction in inflammation, fibroblast count; height and thickness of hypertrophic scar in addition to decrease in immunological scores and the results were nearly comparable to that of topical triamcinolone acetonide.Keywords: Chenopodium murale; Rabbits; Topical phytosterol.